Elementary structures for architects and builders - Shaeffer, R. E. (Upper Saddle River, N.J. : Pearson Prentice Hall, 2007)
"A market leader, Elementary Structures for Architects and Builders, Fifth Edition provides an introduction to building structures and materials, covering essential topics in statics and mechanics of materials, and an introduction to structural analysis and design. Topics include structural properties of area, stress and strain, properties of structural materials, shear and moment, flexural and shearing stresses, deflection and indeterminate beams, beam design and framing, elastic buckling of columns and trusses. Ideal for today's visually oriented student, it offers over 600 illustrations and full-page architectural sketches to clarify text concepts. A comprehensive set of appendices and numerous examples makes it an excellent resource for students and professionals preparing for the architectural registration examination."--pub. desc.
Statics -- Structural properties of areas -- Stress and strain -- Properties of structural materials -- Shear and moment -- Flexural stresses -- Shearing stresses -- Deflection and indeterminate beams -- Beam design and draming -- Elastic buckling of columns -- Trusses.
Keywords: Structural analysis (Engineering); Structural design